Using a fluorine-free copper mesh with dynamically tunable wetting properties for high-flux separation of oil-water mixtures. (December 2021) - Parisi, Gregory; Narayan, Shankar
Abstract: Managing oily wastewater continues to be a significant challenge with the continuous rise in oil extraction and processing, necessitating new and improved technologies to separate oil from water. In this regard, smart materials provide controllable super-wettability to separate either oil or water from their mixture based on the chosen wetting properties of the material. However, several challenges facing smart materials include high cost, low separation fluxes, poor durability, and complex equipment for separation. This study demonstrates the use of a fluorine-free superhydrophobic/superoleophilic copper mesh fabricated using N-(2-Aminoethyl)-11-Aminoundecyltrimethoxysilane. Oil-water separation using this material allows separation fluxes exceeding 80, 000 L/m 2 /h, with separation efficiencies above 90%. This cost-effective and straightforward approach is also durable, as demonstrated via abrasion tests. More importantly, we demonstrate a simple strategy to reversibly switch the wettability of the copper mesh between hydrophilic/oleophobic and hydrophobic/oleophilic states. This strategy allows varying the static water contact angles between 150 o and 0 o . Consequently, oil can be separated from an oil-water mixture using the hydrophobic/oleophilic wetting state, while water can be separated from the oil-water mixture using the hydrophilic/oleophobic wetting state. With further development, this material can address oily wastewater produced in industrial applications and oil-spills. Graphical abstract: Unlabelled Image Highlights: This study uses a fluorine-free copper mesh to separate oil-water mixtures. The copper mesh provides controllable wettability to separate either oil or water. Mesh has the potential to switch between hydrophilic and hydrophobic states. The water contact angles are switchable between 0 and 150 degrees. Oil-water separation fluxes are >80, 000 L/m 2 /h with separation efficiencies >90%.